Peluang Perbankan Syariah Dalam Perekonomian Di Indonesia - Nur Roikhatul Jannah (Journal of Islamic Banking, 2020)
Islamic banking is a banking system developed based on Islamic sharia (law). Indonesia, where the majority of the population is Muslim, provides a large enough room for the development of Islamic banks. The development of Islamic banking has become a measure of the success of the existence of the Islamic economy. Bank Muamalat as the first Islamic bank and a pioneer for other Islamic banks has already implemented the sharia system amid the proliferation of conventional banks. Islamic banks are not new to the banking world. We know that at the end of the 90s, many conventional banks were liquidated due to the monetary crisis, but in fact, Islamic banking was able to survive, develop and continue to exist today. Shari'ah banking is increasingly recognized in the community from day to day. The opportunity for Islamic banking in the future is enormous. However, the opportunity to become a well-established sharia banking cannot be separated from various challenges. All challenges need to be faced, solved so that the right solution is sought for the advancement of Islamic banking. Keywords: Sharia Banking, Opportunities, Challenges